Solventless 3D printed high-temperature resistant cyclosiloxane-containing resin for low-shrinkage ceramization and nano-functional composite development - Zhou, Zihao (2023)
Digital light processing (DLP) 3D printing technology has the advantage of rapid preparation of high-precision complex devices. However, photosensitive resin's insufficient high-temperature resistance and mechanical properties limit its application in aerospace and structural functional devices. Herein, we propose a photosensitive cyclosiloxane-containing resins through thiol-ene click reaction. The UV cured cyclosiloxane-containing resins showed high-temperature resistance (5% weight loss ≈ 400 °C), tunable mechanical properties, low temperature derived ceramics etc. With photosensitive characteristics of the developed systems proven by the photo-rheology studies, printing parameters were calculated by Beer-Lambert's law to achieve precise control of the 3D printed constructs with complex geometries. This study also demonstrates the feasibility of ceramicization of the 3D printed parts and the incorporation of nano-functional materials (MXene, invisible ink) for functional device preparation.